2010
DOI: 10.3233/jad-2010-100630
|View full text |Cite
|
Sign up to set email alerts
|

Is the Urea Cycle Involved in Alzheimer's Disease?

Abstract: Since previous observations indicated that the urea cycle may have a role in the Alzheimer's disease (AD) process, we set out to quantify the expression of each gene involved in the urea cycle in control and AD brains and establish whether these genes could be genetic determinants of AD. We first confirmed that all the urea cycle enzyme genes are expressed in the AD brain. The expression of arginase 2 was greater in the AD brain than in the control brain. The presence of the rare arginase 2 allele rs742869 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 36 publications
(39 reference statements)
7
55
1
Order By: Relevance
“…The accumulation of ammonia in Alzheimer's disease (hyperammonemia) and consequent dyshomeostasis of urea-related metabolites has been associated with reduced glutamine synthetase activity (Seiler, 2002) and enzymatic deficiencies in the urea cycle (Hansmannel et al, 2010). However, the extra decrease found in the IL-4 knockout mice compared with the APP/PS1 mice (although not statistically significant, Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The accumulation of ammonia in Alzheimer's disease (hyperammonemia) and consequent dyshomeostasis of urea-related metabolites has been associated with reduced glutamine synthetase activity (Seiler, 2002) and enzymatic deficiencies in the urea cycle (Hansmannel et al, 2010). However, the extra decrease found in the IL-4 knockout mice compared with the APP/PS1 mice (although not statistically significant, Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Decreased urea content (Table 1) supports a disturbed homeostasis of ammonia via the urea cycle, which may elicit deleterious effects on the central nervous system and has been closely related to AD pathology [39]. Thereby, an abnormal content of urea and related amino acids has been previously found in serum [19,20,33] and brain [8,9] of AD, accompanied by altered levels of expression in different enzymes and the corresponding genes [40]. Other studies reported an increased concentration of inosine in response to an accelerated degradation of nucleotides in brain from human patients [41] and APP/PS1 mice [9], which is finally reflected in peripheral blood as revealed our metabolomic fingerprinting platform.…”
Section: Biological Hypothesismentioning
confidence: 88%
“…The significant reduction in urea levels (Table 4) pointed to a perturbation of the urea cycle, responsible for controlling ammonia concentrations in the organism. In Alzheimer's disease, the alteration of this pathway has been previously demonstrated on the basis of altered levels of expression in different enzymes and the corresponding genes [65]. To conclude changes observed in homocarnosine and glutathione, important antioxidants involved in the defense of the central nervous system, could be related to oxidative damage in brain.…”
Section: Metabolitementioning
confidence: 90%